THE EFFECT OF DEBT DEFAULT, PREVIOUS AUDIT OPINION, LIQUIDITY AND SOLVABILITY ON GOING CONCERN AUDIT OPINIONS FOR 2014 TO 2018 (Case Study on Manufacturing Company Listed on the Indonesia Stock Exchange) - Angelia; Sidharta , Juaniva; Lumbantoruan , Rutman (Universitas Kristen Indonesia, 2020)
Basically, a goingMconcernMopinionlismannopinionngivennbyltheiauditor if the sustainability ofnancompany is in doubt, in providing a going concern opinion an auditor will pay attention tonthenfactorsnthatnare considered toninfluence the issuance ofnthe goingbconcernbopinion. For this reason, thenresearch’sngoals werentonexaminentheneffectnofnauditnopinionnreceivednin debt default, previous year's audit opinion, liquidity and solvability of angoingnconcernsaudit opinions, ThezsampleszofzthiszresearchzwerezthezcompanyzthatzsufferedWlosses two years in a row and listedzin Indonesia StockzExchange in 2014 - 2018. Then the sampling was done by using a purposive sampling method and obtained a sample of 37 companies. The data used in this research is secondary data obtained from the IDX website in the form of financial reports and annual reports. The data were then tested and analyzed with SPSS version 24 through logistic regression analysis. Result of this research showedzthat thezdebt default, previouszyear's auditzopinion and liquidity haszsignificantzeffect, butzthe solvability variables weren’tzsignificantlyzinfluencezwithzgoingzconcernzopinion Keywords: Goingeconcerneauditeopinion, Debt default, previous year's audit opinion, liquidity, solvency